Action plan for the communication process in a nursing team - Priscilla Valladares Broca; Márcia de Assunção Ferreira (Universidade Estadual de Maringá, 2016)
The objective of this study is to propose an action plan for the communication process in the nursing team. The theoretical references were: the model of a communication process proposed by Berlo and essential concepts of King´s Theory. It is a qualitative, convergent-care research. The data production technique was the semi-structured interview with 25 nurses of a public hospital. Data used the thematic content analysis technique. The elements of the communication team are: perception, self, space, time, stress, role, authority, power, status, audience, empathy and nonverbal communication. The plan proposes a dynamic, flexible, interactive and relational communication process, in order to contribute to the professional qualification and make new practices of care viable. It was concluded that its elements do not have a fixed and stable position, but throughout the process they are used according to the needs of each party.